Logic-based program synthesis and transformation : 29th International Symposium, LOPSTR 2019, Porto, Portugal, October 8-10, 2019, Revised selected papers /: 29th International Symposium, LOPSTR 2019, Porto, Portugal, October 8-10, 2019, Revised selected papers. (2020) - Unknown
No abstract available